C. Plinii Cæcilii secundi epistolæ et panegyricus - Pliny the Younger 61-113 (Amsterdam Elsevier, 1659)
The Epistulae ([ɛˈpɪs.t̪ʊ.ɫ̪ae̯], "letters") are a series of personal missives by Pliny the Younger directed to his friends and associates. These Latin letters are a unique testimony of Roman administrative history and everyday life in the 1st century. The style is very different from that in the Panegyricus, and some commentators maintain that Pliny initiated a new genre: the letter written for publication. This genre offers a different type of record than the more usual history; one that dispenses with objectivity but is no less valuable for it. Especially noteworthy among the letters are two in which he describes the eruption of Mount Vesuvius in 79 during which his uncle Pliny the Elder died (Epistulae VI.16, VI.20), and one in which he asks the Emperor for instructions regarding official policy concerning Christians (Epistulae X.96).
Gaius Plinius Caecilius Secundus, born Gaius Caecilius or Gaius Caecilius Cilo (61 – c. 113), better known as Pliny the Younger (/ˈplɪni/), was a lawyer, author, and magistrate of Ancient Rome. Not to be confused with Pliny's uncle, Pliny the Elder, who helped raise and educate him.
Contains index
Ex libris Johannis Palmer 1672Ex libris Charless Lett Feltoe 1881
Keywords: Classical Antiquity (8th Century BC-6th Century AD); 17th Century (1601-1700); Correspondence; Rome (Italy)